Youth Center for Spiritual, Ethical and Social Development: Contribution to the Improvement of the Urban and Regional Environment - Galina M. Romanova; Svetlana V. Petrova; Marina A. Maznichenko; Snezhana V. Brevnova; Nadezhda M. Grigorashchenko-Aliyevа (Высшее образование в России)
The article addresses the problems of formation and implementation of a youth policy at the university aimed at promoting spiritual and moral values, educating a socially responsible person. The authors describe the ways to strengthen the university’s role in the development of local communities, urban and regional environment. These issues are considered on the example of the implementation of the strategic project of Sochi State University “Youth Center for Spiritual, Moral and Social Development”. During its existence, including in the status of the basic university of Krasnodar Region, the university has accumulated considerable experience in developing an active life position among young people through building relationships not only among students, but also between the university and various subjects of the socio-economic, political, spiritual and cultural infrastructure of the region. The project “Youth Center for Spiritual, Moral and Social Development” is a successful experience in uncovering students’ social talents, establishing interaction with the authorities, administration, and social partners in order to solve pressing social problems, to inculcate in the youth spiritual and moral values, to involve young people in social entrepreneurship. The potential of this form of work is revealed in the development of social activity of young people acting in the interests of the whole society.